71.1k views
3 votes
Use the four-step process to find f'(x) and then find f'(1), f'(2), and f'(3).

f(x) = -x^2+6x-5
f'(x) =

1 Answer

6 votes

Step 1: evaluate f(x+h) and f(x)

We have


f(x+h) = -(x+h)^2+6(x+h)-5 = -(x^2+2xh+h^2)+6x+6h-5


= -x^2-2xh-h^2+6x+6h-5

And, of course,


f(x)=-x^2+6x-5

Step 2: evaluate f(x+h)-f(x)


f(x+h)-f(x)=-x^2-2xh-h^2+6x+6h-5-(-x^2+6x-5)=-2xh-h^2+6h

Step 3: evaluate (f(x+h)-f(x))/h


(f(x+h)-f(x))/(h)=-2x-h+6

Step 4: evaluate the limit of step 3 as h->0


f'(x) = \displaystyle \lim_(h\to 0) (f(x+h)-f(x))/(h)=-2x+6

So, we have


f'(1) = -2\cdot 1+6 = 4,\quad f'(2) = -2\cdot 2+6 = 2,\quad f'(3) = -2\cdot 3+6 = 0

User LDMJoe
by
6.3k points